(untitled) (Quest Journal of Management and Social Sciences, 2025)
Background: The financial literacy is a very important life skill that Generation Z needs and especially among management students as they will act as business leaders in the future. Nevertheless, the multidimensional structure of financial literacy of Gen Z in Nepal is under-researched empirically. Purpose: This research will determine the financial literacy rates among Chitwan management students in Nepal who are part of Generation Z as well as explore the impact of financial literacy, attitude, demography, and environmental factors on financial behaviors and outcomes. Design/methodology/approach: A structured questionnaire was used in collecting data on 318 undergraduate and postgraduate students which was adopted as a quantitative research design. The measurement and structural models were tested by using Partial Least Squares-Structural Equation Modeling (PLS-SEM) which has reliability, convergent validity and discriminant validity and hypothesis was tested by using path analysis. Findings: The findings indicate that students have moderate financial knowledge and positive financial attitudes. Financial knowledge, attitudes and environmental factors are strongly predictive of the financial behaviors and financial outcomes and there is no significant direct impact of demographic factors on the same. Environmental factors were found as the best predictors. Conclusion: The results confirm the multidimensionality of financial literacy which aligns with the 3-Pillar Model and the Social Learning Theory and suggest the importance of context-specific financial literacy interventions in the context of management education in Nepal. Keywords: Financial literacy, Gen Z, management students, financial behavior, digital tools